Evaluasi Kelayakan Finansial Bus Trans Metro Pekanbaru Koridor VI Trayek Terminal Bandar Raya Payung Sekaki (BRPS) - Pandau - Emileo, Gegen; Taufik, Hendra; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Trans Metro Pekanbaru (TMP) is a Mass Public Transportation Facility (SAUM) which has been operating since 2009 in Pekanbaru City. Busway is expected to be one solution to overcome the problems of transportation in the Metropolitan City. Pekanbaru City Government should think about the financial aspects of the use of the bus rapid transit. Management of good financial feasibility can minimize any loss incurred from the operation of this public transport. Therefore, it is necessary to evaluate Transmetro's financial viability for corridor VI. Aspects analyzed include Operational Cost of Vehicle (OCV) and financial aspect by analyzing Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), Payback Period (PBP) as well as Analysis Sensitivity. The result of BOK analysis for large TMP buses is Rp.6.578,68. The calculation result from the combination of 30% own capital and 70% of the total investment of TMP bus is Rp,6,379,123,318 with NPV Rp,4,965,068,212. BCR of 1.38 and PBP for 4 years 5 months. Then the sensitivity analysis of the investment increased to 148%, the sensitivity analysis to profit decreased 82%, the sensitivity analysis to the cost increased to 139% and the sensitivity to interest analysis increased by 28.05%. The result of the investment evaluation can be concluded that the investment is financially feasible.Keywords: Trans Metro Pekanbaru (TMP), Corridor VI, Analysis of Financial, Vehicle Operating Costs (VOC), Investment, Pekanbaru City